APECED: A Paradigm of Complex Interactions between Genetic Background and Susceptibility Factors - De Martino, Lucia; Capalbo, Donatella; Improda, Nicola; D' Elia, Federica; Di Mase, Raffaella; D’Assante, Roberta; D' Acunzo, Ida; Pignata, Claudio; Salerno, Mariacarolina (Frontiers in Immunology, 2013)
Autoimmune polyendocrinopathy candidiasis ectodermal dystrophy (APECED) is a rare autosomal recessive disease, caused by mutations of a single gene named Autoimmune regulator gene (AIRE) which results in a failure of T cell tolerance. Central tolerance takes place within the thymus and represents the mechanism by which potentially autoreactive T cells are eliminated through the negative selection process. The expression of tissue-specific antigens (TSAs) by medullary thymic epithelial cells (mTECs) in the thymus is a key process in the central tolerance and is driven by the protein encoded by AIRE gene, the transcription factor autoimmune regulator (Aire). A failure in this process caused by AIRE mutations is thought to be responsible of the systemic autoimmune reactions of APECED. APECED is characterized by several autoimmune endocrine and non-endocrine manifestations and the phenotype is often complex. Although APECED is the paradigm of a monogenic autoimmune disorder, it is characterized by a wide variability of the clinical expression even between siblings with the same genotype, thus implying that additional mechanisms, other than the failure of Aire function, are involved in the pathogenesis of the disease. Unraveling open issues of the molecular basis of APECED, will help improve diagnosis, management and therapeutical strategies of this complex disease.